PENGARUH PENYULUHAN GIZI TERHADAP PENGETAHUAN DAN PRAKTEK GIZI IBU NIFAS DI WILAYAH PUSKESMAS LIKUPANG KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA - Jufri Sineke; Yohanis Tomastola; Kristina Nanangkong (Jurnal GIZIDO, 2013)
Mothers who consumed dietary restrictions due to cultural taboo food intake leads tolow nutrient substances . This situation is often exacerbated by the lack of goodmaternal nutrition knowledge so that mothers are willing to follow the restrictions thatexist . This study aimed to determine the effect of nutrition education on nutritionknowledge and practices of puerperal women in the East Regional Health CenterLikupang .This research is quasi-experimental study ( quasi Experimental ) to designone group pre and post test design . The research was conducted in June- July 2012. Number of samples 96 . Collecting data using questionnaires and 24 hours foodrecall and food frequency form . Data processing with SPSS version 16 . Dataanalysis using t - test . The results showed that the significant effect of nutritioncounseling on nutrition knowledge and practices of puerperal women ( P<0.05 ) .Energy intake postpartum women who received counseling did not significantly ( p>0:05 ) . Postpartum maternal protein intake is very significant influence ( p< 0.05), .No conclusions on the influence of nutrition counseling nutrition knowledge andpractice of postpartum mothers . Intake of nutrients and energy it does not influencethe effect of nutritional counseling on nutrient intake of protein .